Faktor-Faktor Yang Mempengaruhi Profitabilitas Bank Umum Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Pasaribu, Dompak (Jurnal Mahkota Bisnis (Makbis), 2022)
This study aims to determine the effect of Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Operational Costs / Operating Income (BOPO) and Non Performing Loans (NPL) on Return On Assets (ROA) Banking listed on the Indonesia Stock Exchange (IDX). This research period is 2015-2018. This type of research is causal quantitative research and the source of data used is secondary data. Data analysis techniques used multiple linear regression. Data collection methods consist of documentation and library studies. As well as the sampling technique through the purposive sampling method and research data obtained 43 banks listed on the Indonesia Stock Exchange (IDX) as a population and as many as 17 banks listed on the Indonesia Stock Exchange (IDX) as samples. The results of this study indicate: Loan to Deposit Ratio (LDR) has a positive and not significant effect on Return on Assets, Capital Adequacy Ratio (CAR) has a positive and significant effect on Return on Assets (ROA), Net Interest Margin (NIM) has a negative effect and does not significant on Return On Assets (ROA), Operating Costs / Oprasional Revenues (BOPO) have a negative and significant effect on Return On Assets (ROA), Non Performing Loans (NPL) have a negative and significant effect on Return On Assets (ROA), simultaneously LDR , CAR, NIM, BOPO and NPL have positive and significant effect on Return On Assets (ROA) of commercial banks listed on the Indonesia Stock Exchange (BEI) in 2015-2018. This also shows that 84% of ROA is influenced by LDR, CAR, NIM, BOPO and NPL while the remaining 16% is influenced by other variables not examined in this study.